An empirical investigation of automation technology as material waste mitigation measure at Johor construction sites - Abkar, Mahdi Mohammed Abdullah; Yunus, Riduan; Al-Shameri, Ahmed Saleh Ahmed Saif; Harouache, Ahmed; Gamil, Yaser (Frontiers in Built Environment, 2023)
Automation Technology (AT) in the construction industry is the use of advanced tools, devices, and processes that reduce manual labour and enhance efficiency in various construction activities. Automation technology can minimize waste, optimize resource utilization, and reduce the environmental impact of construction processes. This study aims to examine the relationship between Automation Technology Adoptions (ATA) utilizing Reduce, Reuse and Recycle 3R, Building Information Modelling BIM, Industry Building System IBS, Green Building Index GBI and Internet of Things IoT, towards Construction Site Performance (CSP) to measure their influences on material waste mitigation measures at Johor construction sites. To achieve these goals, 5 hypotheses were developed to explore the association between ATA and CSP. Data was gathered utilizing an online survey method. The participants are contractors and expertise practitioners in the Johor construction industry such as architects, project managers, and academicians /researchers. A total of 257 responses were valid to investigate the assumptions of the validations. Partial Lease Square -Structural Equation Modeling (PLS-SEM) procedure was used. The findings revealed that ATA utilizing 3R, BIM, IBS, GBI, and IoT as material mitigation measures is positively enhancing the construction site performance.